Brics Ascendancy: Challenging Western Hegemony in a Globalized World (International Journal of Scientific Research and Management (IJSRM), 2024)
The global financial milieu has long been characterized by the pre-eminence of the United States dollar as the world’s principal reserve currency. Nevertheless, emerging trends indicate the prospect of a paradigmatic shift wherein the dollar’s status as a reserve currency may diminish. This study undertakes an in-depth analysis of the factors contributing to this potential transition, with particular emphasis on the ascent of the BRICS nations (Brazil, Russia, India, China, and South Africa) and their capability to establish a novel financial framework. Drawing upon insights from eminent scholars affiliated with prestigious institutions such as Harvard, Cambridge, Princeton, Chicago, Yale, and Oxford, this research assesses the evolving dynamics of global finance. By scrutinizing historical hegemonic patterns dating back to the 17th century, this investigation offers a comprehensive perspective on the ascendance and decline of dominant currencies and their ramifications on the international monetary system. Through meticulous examination of economic indicators, geopolitical transformations, and institutional advancements, this paper elucidates potential avenues through which the BRICS nations could challenge the hegemony of the U.S. dollar. Furthermore, it explores the feasibility of instituting alternative financial mechanisms to facilitate transactions and investments among BRICS countries and beyond, thereby mitigating dependence on the dollar-centric financial framework. This research, therefore, has culminated in the conclusion that the hegemonic status of the U.S. dollar is poised to diminish before the year 2030.